2022
DOI: 10.3390/ijms231911157
|View full text |Cite
|
Sign up to set email alerts
|

Response of Rice with Overlapping Growth Stages to Water Stress by Assimilates Accumulation and Transport and Starch Synthesis of Superior and Inferior Grains

Abstract: Drought stress at jointing–booting directly affects plant growth and productivity in rice. Limited by natural factors, the jointing and booting stages of short-growth-period rice varieties are highly overlapped in high-latitude areas, which are more sensitive to water deficit. However, little is known about the dry matter translocation in rice and the strategies of starch synthesis and filling of superior and inferior grains under different drought stress was unclear. In this study, the rice plants were subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The reduction in the number of tillers and the number of grains in the spike resulted in yield loss, which is consistent with the results of this study. Studies have reported that drought stress at the jointing-booting stage can lead to stagnant growth, limited photosynthesis, reduced accumulation of photosynthetically active products, and impeded nutrient translocation, thereby reducing rice yield and quality [8,49]. In this study, the P3 treatment had the lowest thousand grain weight and fruiting rate because continuous drought stress from the heading-flowering stage affects the development and functioning of the reproductive organs of rice [50].…”
Section: Discissionmentioning
confidence: 74%
“…The reduction in the number of tillers and the number of grains in the spike resulted in yield loss, which is consistent with the results of this study. Studies have reported that drought stress at the jointing-booting stage can lead to stagnant growth, limited photosynthesis, reduced accumulation of photosynthetically active products, and impeded nutrient translocation, thereby reducing rice yield and quality [8,49]. In this study, the P3 treatment had the lowest thousand grain weight and fruiting rate because continuous drought stress from the heading-flowering stage affects the development and functioning of the reproductive organs of rice [50].…”
Section: Discissionmentioning
confidence: 74%
“…The TGW-Pa values obtained under flooded and AWD conditions exceeded those reported for pigmented rice by Rungrat and Poothab [ 30 ] by 11.2% and 5.5%, respectively. Furthermore, a two-year study conducted by Wang et al [ 31 ] evaluated two japonica rice varieties under water deficit, reporting average values for TGW-Pa ranging from 23.6 to 25.2 g and from 22.9 to 24.4 g under mild and severe drought stress, respectively. These values were notably lower than those obtained in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In the booting stage, flowering stage and filling stage, mild drought increased the starch content of rice (NJ9108) by 1.11%, 2.52% and 3.54%, while severe drought decreased the starch content by 12.49%, 8.87% and 5.86% [19]. Severe drought at the jointing stage reduced the amylose content of rice (SJ6) by 15.61% and increased amylopectin content by 7.21% [20]. Moderate drought stress increased the accumulation of Arabidopsis proline by 6.4 times, anthocyanin by 2.9 times and soluble sugar by 1.7 times [21].…”
Section: Introductionmentioning
confidence: 99%